Reduction of Broiler House Malodor by Direct Feeding of a Lactobacilli Containing Probiotic - Chang, M.H.; Chen, T.C. (International Journal of Poultry Science, 2003)
Studies were conducted to investigate the direct feeding of a lactobacilli containing probiotic, Ecozyme, on broiler house malodor. Results indicated that feeding a diet containing the probiotic decreased (P